2021
DOI: 10.54113/j.sust.2021.000004
|View full text |Cite
|
Sign up to set email alerts
|

A review of mechanical behavior of structural laminated bamboo lumber

Abstract: The transition of the construction sector to sustainable development mostly depends on the environmental friendliness of building materials. This, in turn, calls for the development of new, strong, and sustainable materials that would be a worthy alternative for traditional materials, including wood. Over the past decade, laminated bamboo lumber (LBL) has received much attention from engineers, practitioners, and scientists for its attractive mechanical properties, comparable to and in some cases superior to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 67 publications
(113 reference statements)
0
30
0
2
Order By: Relevance
“…To reduce the carbon footprint of the built environment [ 5 ], waste wood and recycled plastics can be used as raw materials to produce environmentally friendly WPC, which can meet the performance requirements of construction [ 6 , 7 , 8 ]. Green transformation of the construction industry depends on the environmental friendliness of building materials [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the carbon footprint of the built environment [ 5 ], waste wood and recycled plastics can be used as raw materials to produce environmentally friendly WPC, which can meet the performance requirements of construction [ 6 , 7 , 8 ]. Green transformation of the construction industry depends on the environmental friendliness of building materials [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…LBL is made by stacking and gluing uniformly milled bamboo elements, producing a uniform element shape, size, and orientation in the product. The average strength of structural LBL is similar to flattened bamboo and hardwoods [ 62 ]. Several studies have demonstrated the unique properties of structural LBL [ 62 , 63 , 64 , 65 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…The average strength of structural LBL is similar to flattened bamboo and hardwoods [ 62 ]. Several studies have demonstrated the unique properties of structural LBL [ 62 , 63 , 64 , 65 , 66 ]. Structural members made of LBL can be created in any cross-section and shape and are adaptable to different heights and spans of members.…”
Section: Resultsmentioning
confidence: 99%
“…They have been replaced by artificial boards such as oriented strand board (OSB) and laminated veneer lumber (LVL). This effectively alleviates the waste of high-quality wood and makes full use of the excellent mechanical properties of wood-based panels (Cui 2014;Dauletbek et al 2021;Su et al 2021;Yang et al 2021).…”
Section: Introductionmentioning
confidence: 99%